Livestock farmers’ perception on effect of climate change on smallholder dairy farming in Fiji - Igbal, Mohammed Rasheed; Sagero, Philip Obaigwa; Magiri, Royford Bundi (Frontiers in Climate, 2026)
This study investigated the impacts of climate change on smallholder dairy farming in Fiji through a mixed-methods approach, combining a survey of 242 farmers in Viti Levu’s Central Division with long-term meteorological and milk production data. Farmers were predominantly male (94.2%), aged over 54 years (73.1%), with low formal education (83.0% primary or secondary) and annual incomes below FJD 10,000 (43.4%), operating small farms (81.8% on 0.4–8.1 ha) with fewer than 20 milking cows (73.6%). Most farmers perceived rising daytime (70.2%) and nighttime (56.6%) temperatures and declining rainfall amounts and duration in both wet and dry seasons over the past 15 years. They reported substantial climate-induced impacts, including forage disappearance (73.6%), increased parasites and diseases (76.0%), reduced water availability (65.7%), and lower milk production (61.1%), compounded by potential inbreeding effects from disease control measures. Key adaptation challenges included pasture loss (64.9% high effect), deteriorated water quality (55.4%), and reduced milk yield (52.0%). Farmers primarily obtained climate information through peer networks (mean importance 4.5) and media (3.7), with limited input from research institutions or universities. Meteorological analysis (1970–2020) confirmed significant warming trends in maximum and minimum temperatures (Sen’s slope 0.01–0.04 °C/year at most stations), aligning with farmers’ perceptions, but revealed no significant long-term rainfall trends despite high interannual variability driven by ENSO. Tropical cyclones remained frequent, predominantly lower-intensity categories. National milk production declined significantly from 9.5 million liters in 2012 to 6 million liters in 2021, likely exacerbated by heat stress, rainfall variability, and socio-economic constraints. These findings highlight the vulnerability of Fiji’s smallholder dairy sector to climate change and underscore the urgent need for targeted adaptation strategies, including heat-tolerant breeds, resilient pastures, improved water management, enhanced extension services, and inclusive policies addressing demographic and economic barriers in rural area.